ADVANCES IN RICE IPM - INDIAN SCENARIO - GURURAJ KATTI, CHINTALAPATI PADMAVATHI, CHITRA SHANKER and (The Journal of Research, PJTSAU, 2019)
India has the largest area under rice in the world and is grown in extremely diverse environments. Of the 42 million ha of rice area, about 42% is under irrigated ecosystem, 35.5% rain fed lowland, 16.8% rainfed upland and 5.7% is flood-prone/ deep water ecosystem. Rice was grown in an area of 42.6 million hectares with a production of 104.80 million tonnes during 2014-15 (Directorate of Economics and statistics, DAC, GOI - http://eands.dacnet.nic.in/ ). In order to meet the growing demand of the ever increasing population, we need to produce 156 million tonnes of rice by 2030. But the rice production is limited by both abiotic and biotic stresses of which insect pests alone cause about 25% losses amounting to Rs. 2,40,138 (Two lakhs forty thousand and one hundred and thirty eight million rupees) (Dhaliwal et al. 2010). Over 100 species of insects have been reported to attack and feed rice crop from nursery to maturity and also in storage.